THE POTENTIAL OF THE SPICE ROUTE AS AN INSTRUMENT OF NATION BRANDING AND PROMOTION FOR INDONESIA: A SWOT ANALYSIS - Kriswandwitanaya, Muhammad Farhan; Akim, Akim; Dermawan, Windy (Universitas Jenderal Ahmad Yani, 2025)
Indonesia's Spice Route, historically a vital trade network, is now being strategically leveraged for nation branding, cultural diplomacy, and economic promotion. This study employs a SWOT analysis to evaluate Indonesia's strengths, weaknesses, opportunities, and threats in revitalizing the Spice Route. Findings highlight Indonesia’s rich spice heritage, government initiatives such as Indonesia Spice Up the World, and efforts to gain UNESCO recognition as key strengths. However, challenges include low productivity, inconsistent quality control, and competition from other spice-exporting nations. Opportunities lie in increasing global demand for sustainable spices and enhanced digital trade, while threats include regulatory barriers and fragmented stakeholder coordination. To maximize the Spice Route's potential, Indonesia must integrate cultural diplomacy, sustainable trade, and tourism strategies. This research contributes to discussions on nation branding, public diplomacy, and economic competitiveness, providing insights for policymakers and industry stakeholders.